Evaluasi Tingkat Kepuasan Pasien JKN (Studi Pengguna Aplikasi JKN Mobile di Karawang) - Suherman, Enjang; Sumarni, Neni; Suroso, Suroso (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
The purpose of this study is to evaluate the satisfaction level of patients using the Mobile JKN application in Karawang. The research method uses a descriptive quantitative approach with the population consisting of patients who use the Mobile JKN application in Karawang. The sampling technique applied is Snowball sampling, where respondents refer other respondents, gradually increasing the sample size. This sampling method was chosen due to the unknown population of patients using the JKN application. Data analysis was conducted using the Importance-Performance Analysis (IPA) method and a 1-5 scale for the survey. The research results showed that the overall satisfaction level of users of the Mobile JKN application reached 94%, with the most satisfying indicator being the ease of accessing the application through various internet service providers (103%), and the lowest indicator being the ease of obtaining information about doctor schedules and inpatient services (83%). Based on the Cartesian diagram analysis, there are four quadrants illustrating the service improvement priorities: (1) Priority for improvement, (2) Maintain performance (meets expectations), (3) Low priority, and (4) Overperformed. The findings show that although most users are satisfied with the application, some aspects, such as information on schedules and inpatient rooms, need improvement.